A Review on Metallic Nanoparticles: A Noble Approach on Drug Delivery System - Dewan , Debajit; Ghosh , Parag (Advanced Concepts in Pharmaceutical Research Vol. 1, 2023)
Over the past few years, diagnosis and treatment of various diseases have become a significant challenge due to drug resistance, poor bioavailability, drug toxicity and high medication costs. Maximum drugs are hydrophobic in nature, and their efficacy depends on the route of administration. Hence, finding a new drug delivery system is essential for improving drug absorbability, pharmacokinetics, metabolism, metabolic effect duration, and minimizing toxicity. These days, the application of nanotechnology, such as nanoparticle nanomaterial, leaves a golden trail in the health sector. Nanomaterials differ from bulk materials of the same composition due to their distinctive physicochemical features, such as their small size, high surface area to mass ratio, and high reactivity. Nanoparticles (NPs) are divided into categories based on shape, size, nature, and composition like metallic nanoparticles (MNPs), porous nanoparticles, mesoporous nanoparticles, carbon nanotubes etc. Various metals and nonmetals, like silver, gold, silicon, and calcium phosphate, are used in nanoparticle preparation for anticancer, anti-microbial, bone regeneration etc. Not only the biomedical sector, metallic nanoparticle also has primary functions in textiles, the agriculture industry etc. The drawback of metallic nanoparticles is that they are prepared by toxic chemicals and require high energy. Some MNPs also posses has several toxicities. The alternative way to prepare metallic nanoparticles is using by plants, bacteria and fungi. Green synthesis is a promising way that allows low energy and low cost with less toxicity. This review gives an overview of metallic nanoparticles used in drug delivery systems.